The Jambur Karo Building View from The Lens of Disability Concerning Local Action Plan for Persons with Disabilities - P. Tariga, Nuah (ADI Publisher, 2021)
Jambur is a public meeting building in the Karo Batak tribe, or just called Karo, which has a robust kinship system and can see it from the architecture of the traditional building. Even in realizing the building by using the community's approach, it becomes an empowering process for all procedures. We see that deliberation for consensus is not something impossible which is not just lip service. The principles of genuine and open democracy took place, but that only happened in the past, maybe. Because it turns out that we build no longer with the heart and character but with an approach that is often consumptive and hedonistic, this has become a very extreme and blind problem. We see it in terms of personal character development and Karo community both in Jakarta, Medan, including cities in Tanah Karo such as Kaban-Jahe and Berastagi, and others. Is there any concern or equity for vulnerable or marginalized communities in the design and planning process? Let us build it together. Nothing is impossible. Can the regional action plan be developed regarding the accessibility of physical buildings such as jambur or public meeting buildings? Can it be implemented? Furthermore, is it compatible with the National Action Plan for Persons with Disabilities? So that everything can be well coordinated.